The diet and benign paroxysmal positional vertigo (DaBC) study: protocol and baseline characteristics of a prospective cohort investigating dietary patterns and BPPV prognosis—the role of genetics and gut microbiota - Xing, Juanli; Shan, Hongying; Xu, Xinyu; Shi, Wenyan; Ren, Peihua; Wu, Jiaqian; Ma, Le; Mi, Baibing (Frontiers in Nutrition, 2025)
BackgroundAs the prevalent cause of dizziness, benign paroxysmal positional vertigo (BPPV) is increasingly considered a major public health concern due to its high recurrence rate and persistent symptoms. Growing evidence suggests a biologically plausible link between dietary factors and BPPV progression. However, current research on the role of diet in BPPV has predominantly focused on individual nutrients and disease onset, with limited evidence regarding the impact of overall dietary patterns on post-treatment clinical outcomes, especially in Asian populations. Furthermore, the potential interactions among diet, genetic predispositions, and gut microbiota in relation to BPPV prognosis remain insufficiently understood and warrant further investigation. In this study, we conducted a prospective cohort of patients with BPPV in the Chinese population to evaluate the association between post-treatment dietary patterns and their changes, with the recurrence risk of BPPV, and long-term symptoms after standardized reposition therapy, as well as to investigate the potential modifying roles of genetic variations and gut microbiota.Methods/designThe Diet and BPPV Cohort Study (DaBC) was initiated in July 2023 and is an ongoing multicenter prospective cohort study conducted at three specialized neuro-otology centers in Northwest China. Participants underwent comprehensive baseline assessments including medical history, otoneurological evaluations, dietary intake via a validated semi-quantitative food frequency questionnaire (FFQ), psychological status, balance function, and biomarker collection (blood and fecal samples for genotyping and gut microbiota profiling). Follow-up assessments will be scheduled at 1 month and annually for 5 years post-baseline. The primary outcome is defined as the number of BPPV relapses during the 5-year follow-up, while secondary outcomes include average recurrence intervals and patient-reported symptom burdens such as dizziness handicap, anxiety, depression, and sleep disturbances. By October 30, 2024, a total of 844 first-diagnosed BPPV patients and complete baseline data were enrolled. We describe the study design and present baseline characteristics of the participants enrolled in the cohort to date.DiscussionWith multi-Omics Framework of DaBC Cohort Study, our future findings are anticipated to yield valuable epidemiological evidence regarding the role of diet in BPPV outcomes, which may provide foundational insights to inform clinical recommendations and refine patient management strategies.